2012
DOI: 10.1111/j.2042-3306.2012.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular response during lungeing exercise in horses with lone atrial fibrillation

Abstract: Summary 10Reasons for performing the study: Atrial fibrillation (AF) is the most important dysrhythmia 11 affecting performance in horses and has been associated with incoordination, collapse and 12 sudden death. Limited information is available on ventricular response during exercise in 13 horses with lone AF. 14 Objectives: To investigate ventricular response in horses with lone AF during a standardised 15 lungeing exercise test. Results: Individual average heart rate during walk ranged from 42 to 175 bpm, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 36 publications
7
62
1
1
Order By: Relevance
“…Our study identified an extreme increase in HR in the horses during exercise. This finding is in agreement with a previous study, in which a HR of up to 492 bpm was recorded in horses in AF during a submaximal lunging test . A submaximal exercise test performed in warmblood horses in AF also showed an increased HR compared with healthy controls, but it was not as high as the other reported values and our findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study identified an extreme increase in HR in the horses during exercise. This finding is in agreement with a previous study, in which a HR of up to 492 bpm was recorded in horses in AF during a submaximal lunging test . A submaximal exercise test performed in warmblood horses in AF also showed an increased HR compared with healthy controls, but it was not as high as the other reported values and our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The irregular electrical conduction from atria to ventricles as well as the exceedingly fast ventricular response rate during AF have profound effects on ventricular electrophysiology. Three of the 6 horses showed a high number of wide complex tachycardias with R‐on‐T morphology during exercise, and this high prevalence is in agreement with a previous study . In normal Standardbred trotters, the prevalence of single abnormal QRS complexes during racing has been reported at between 0% and 4%, whereas the prevalence in the immediate period after racing is approximately 20% .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A modified base-apex configuration as described by Verheyen et al (lead II) was used [8]. A modified base-apex configuration as described by Verheyen et al (lead II) was used [8].…”
Section: Electrocardiographymentioning
confidence: 99%
“…; Physick‐Sheard and McGurrin ; Verheyen et al . ). Caution and circumspection and careful attention to data quality are essential.…”
Section: The Ecg Heart Rate and Rhythm Analysismentioning
confidence: 97%